Characteristics of Micro‐Nano Bubbles and Potential Application in Groundwater Bioremediation. (1st September 2014) - Li, Hengzhen; Hu, Liming; Song, Dejun; Lin, Fei
ABSTRACT: : Content of oxygen in water is a critical factor in increasing bioremediation efficiency for contaminated groundwater. Micro‐nano bubbles (MNBs) injection seems to be an effective technique for increasing oxygen in water compared with traditional air sparging technology with macrobubbles. Micro‐nano bubbles have larger interfacial area, higher inner pressure and density, and lower rising velocity in water, superior to that of macrobubbles. In this paper, MNBs with diameters ranging from 500 nm to 100 μm are investigated, with a specific focus on the oxygen mass transfer coefficient from inner bubbles to surrounding water. The influence of surfactant on the bubbles formation and dissolution is studied as well. The stability of MNBs is further investigated by means of zeta potential measurements and rising velocity analysis. The results show that MNBs can greatly increase oxygen content in water. Higher surfactant concentration in water will decrease the bubbles size, reduce the dissolution rate, and increase the zeta potential. Moreover, MNBs with greater zeta potential value tend to be more stable. Besides, the low rising velocity of MNBs contributes to the long stagnation in water. It is suggested that micro‐nano bubble aeration, a potential in groundwater remediation technology, can largely enhance the bioremediation effect.